Nonlinear association between pre-pregnancy body mass index and preterm birth in singleton pregnancies conceived with assisted reproductive technology - Zhuang, Tingting; Sun, Jingli; Zhang, Yu (Frontiers in Nutrition, 2026)
ObjectiveThis study aimed to analyze the correlation between pre-pregnancy body mass index (BMI) and the risk of preterm birth (PTB) in the assisted reproductive technology (ART) population and to determine the optimal BMI associated with the lowest risk of PTB.DesignRetrospective cohort study.SettingThe National Vital Statistics System birth dataset (January 1, 2019–December 31, 2023) from the National Center for Health Statistics in the United States.SubjectsFor birth data from 2019 to 2023, women who conceived via ART, with a single live birth, age at delivery ≥18 years and gestational age at delivery of 24 to 41 weeks were included. Women with missing data were excluded. The study included a total of 197,237 women with an average age of 35 ± 5 years.ExposurePre-pregnancy BMI.Main outcome measuresThe primary outcome is PTB (<37 weeks). Evaluate the relationship between pre-pregnancy BMI and PTB by adjusting the logistic regression model for confounding variables; using a 4-node restricted cubic spline (RCS) model to assess nonlinear associations; subgroup analysis was performed based on with or without previous termination or fetal loss; finally, sensitivity analysis was conducted to validate the robustness of the results.ResultsA nonlinear association was observed between pre-pregnancy BMI and PTB (P for nonlinearity: <0.001). The risk of PTB increases at both low and high BMI levels, with the lowest risk of PTB occurring at approximately 21.6 kg/m2 [95% confidence interval (CI): (21.3–21.9)]. Subgroup analysis based on with or without previous termination or fetal loss revealed that the lowest risks of PTB were 22.6 kg/m2 (95% CI: 22.3–22.8) and 21.2 kg/m2 (95% CI: 20.8–21.6), respectively. The results of the sensitivity analyses remained stable.ConclusionA nonlinear association between pre-pregnancy BMI and PTB was observed in women treated with ART. Lower and higher BMIs were associated with an increased risk of PTB, respectively, with the optimal pre-pregnancy BMI associated with the lowest risk of PTB being approximately 21.6 kg/m2. The lowest point may vary depending on whether there was a previous termination or fetal loss.